The Properties of cement brick containing POFA and Cockle Shell as Replacement Material - Shaharin, Nur Dini Arina; Mohd Yassin, Nurain Izzati (Recent Trends in Civil Engineering and Built Environment, 2025)
The rapid increase in building construction in Malaysia for 2023 has led to an increase in the use of natural aggregate resources such as stone and sand for building development. This has led to researchers exploring alternative materials to replace natural materials in cement brick production. In this study, palm oil fuel ash (POFA) and cockle shell were used as replacement materials in cement brick production. The objective was to determine the strength of cement bricks with different percentage of cockle shell, identify the initial rate absorption and water absorption. The experiment involved 20% POFA content combined with 10%, 20%, and 30% cockle shells. The results showed that 10% of the replacement cockle shell produced the highest compressive strength value, meanwhile 30% and 10% were the highest replacement percentages for water absorption and initial rate absorption respectively. This experimental study may be beneficial to  achieve sustainability environment.